2002
DOI: 10.1002/ana.10396
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying PTEN regulation of vascular endothelial growth factor and angiogenesis

Abstract: Inactivation of the tumor suppressor gene PTEN and overexpression of VEGF are two of the most common events observed in high-grade malignant gliomas. The purpose of this study was to determine whether PTEN controls VEGF expression in gliomas under normoxic conditions. Transfer of PTEN to human glioma cells resulted in the transduction of a functional PTEN protein as evidenced by the upregulation of p27 and modification of the phosphorylation status of Akt. Under normoxic conditions, enzyme-linked immunosorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 25 publications
4
40
0
Order By: Relevance
“…33 A novel finding was the histopathology, which also showed an unusually dense number of Schwann cells and blood vessels in the affected soft tissue biopsies and a large number of cells that were immunostained by the S100 antibody that was similar to a report by GomezManzano et al 34 The PTEN gene and promoter were sequenced because germline PTEN mutations were found in 20% of patients with Proteus and Proteus-like syndromes. 20 This study identified a novel PTEN promoter mutation in a highly conserved region positioned between two putative transcription factor binding sites.…”
Section: Discussionsupporting
confidence: 62%
“…33 A novel finding was the histopathology, which also showed an unusually dense number of Schwann cells and blood vessels in the affected soft tissue biopsies and a large number of cells that were immunostained by the S100 antibody that was similar to a report by GomezManzano et al 34 The PTEN gene and promoter were sequenced because germline PTEN mutations were found in 20% of patients with Proteus and Proteus-like syndromes. 20 This study identified a novel PTEN promoter mutation in a highly conserved region positioned between two putative transcription factor binding sites.…”
Section: Discussionsupporting
confidence: 62%
“…In contrast, PTEN-induced downregulation of vascular endothelial growth factor (VEGF) results from decreased activity of the VEGF promoter (Koul et al, 2002;Gomez-Manzano et al, 2003). To determine whether PTEN regulates IGF-IR expression at the transcriptional or post-transcriptional level, we measured steady-state levels of IGF-IR mRNA in NEO-and PTEN-overexpressing clones.…”
Section: Pten Inhibits Igf-ir Precursor Translation In Prostate Cancementioning
confidence: 99%
“…Several studies have indicated that loss of tumor suppressors in tumors can lead to an altered phenotype in which the activities of angiogenic inducers increase relative to the activities of angiogenic inhibitors (Igarashi et al, 2002;Gomez-Manzano et al, 2003). This phenotypic change is called the angiogenic switch, a consequence of which is that transformed cells initiate the process of tumor neovascularization.…”
Section: Introductionmentioning
confidence: 99%